Tajallī or the Computational Theory of Mind? Reconstructing the Ontology of Consciousness in Islamic Philosophy and Cognitive Science - Fahim Zenab Moghimi; Mohammad Dawood Alawi; Adam Shah Hassani; Romzie Foroughi (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2026)
The ontology of consciousness in contemporary debates arises from the tension between the metaphysical paradigm of Islamic philosophy and the physicalist approach in cognitive science, particularly regarding the explanation of qualia, intentionality, and the unity of conscious experience. In Islamic philosophy, the concept of tajallī views consciousness as a hierarchical manifestation of existential reality. In contrast, the computational theory of mind views mentality as the result of symbolic computation and neuronal processes grounded in physical systems. The absence of an integrative framework that explains the relationship between the phenomenological dimension and causal mechanisms leaves the dialogue between the two paradigms fragmented. This study aims to reconstruct a non-reductionist ontology of consciousness through a model of reality stratification that connects the metaphysical and computational dimensions without eliminating the differences in their ontic levels. The study uses a qualitative approach based on literature reviews, employing philosophical hermeneutics, ontological analysis, and comparative-integrative analysis of the main texts of Islamic philosophy, especially the concept of tajallī, as well as the latest cognitive science literature on computationalism, representationalism, and predictive processing. The results of this study indicate that tajallī operates within a gradational ontology that positions consciousness as an intensification of being with a relational-intentional structure. In contrast, computational theories of mind tend to be reductionistic, treating consciousness as a causal output of symbol manipulation and neuronal activity. The proposed reconstruction yields a stratified ontological model that accounts for the compatibility between phenomenal experience and causal explanation without reducing consciousness to a purely physical entity. This model broadens the horizon of dialogue between Islamic philosophy and contemporary consciousness studies and offers a conceptual alternative to the dominance of physicalism in consciousness theory.